2000
DOI: 10.2307/2601000
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Pressure: The Effects on Investments in Product and Process Innovation

Abstract: I analyze the effects of competitive pressure on a firm's incentives to invest in product and process innovations. I present a framework incorporating the selection and adaption effects of product market competition on efficiency and the Schumpeterian argument for monopoly power. The effects of competition on a firm's innovations depend on whether a firm is complacent, eager, struggling, or faint, which is determined by the firm's efficiency level relative to that of its opponents. Finally, the following trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
149
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(164 citation statements)
references
References 17 publications
(17 reference statements)
8
149
0
3
Order By: Relevance
“…The falling productivity of frontier firms is an additional cost of protection emerging from this paper that adds to the loss in domestic consumer surplus and the sub-optimal levels of exit. These empirical results are consistent with recent theoretical findings that have pointed at the relationship between market size (Lileeva and Trefler, 2007), product market competition (Aghion et al 2005, Boone, 2000, temporary tariff protection and the adoption speed of new technology (Miyagiwa and Ohno, 1995;Ederington and McCalman, 2007). An interesting future line of research would be to engage in more in depth industry studies to explore the channels through which productivity changes at the firmlevel in response to trade policy are made.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The falling productivity of frontier firms is an additional cost of protection emerging from this paper that adds to the loss in domestic consumer surplus and the sub-optimal levels of exit. These empirical results are consistent with recent theoretical findings that have pointed at the relationship between market size (Lileeva and Trefler, 2007), product market competition (Aghion et al 2005, Boone, 2000, temporary tariff protection and the adoption speed of new technology (Miyagiwa and Ohno, 1995;Ederington and McCalman, 2007). An interesting future line of research would be to engage in more in depth industry studies to explore the channels through which productivity changes at the firmlevel in response to trade policy are made.…”
supporting
confidence: 91%
“…4 Finally, our results can also be usefully compared to recent work by Aghion et al (2005) who showed that a reduction in product market competition reduces the technology gap in an industry. Also, Boone (2000) shows that when firms operate under weak product market competition, the incentive to innovate in such markets is stronger for less efficient firms. The intuition underlying this result is that with weak competition, strategic effects between firms are smaller than under tough competition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Boone (2000) …nds that when competition is weak, the incentives of less e¢ cient …rms to innovate increase. However, when competition becomes more intense, the incentives of e¢ cient …rms to innovate grow.…”
Section: Introductionmentioning
confidence: 99%
“…Two concurrent views have emerged in this respect. According to one stream of literature, under increased competition companies close to the technology frontier are incentivized to innovate and to increase performance; the opposite holds for laggard companies that, regardless what they do, expect to loose market to more efficient entrants (Boone 2000, Aghion et al 2005. The corporate governance literature indicates that the efficiency level of a firm, at its turn, depends on the ownership structure (see the survey of Lawriwsky 1984).…”
Section: Introductionmentioning
confidence: 99%